CLIMATE OF ORGANIZATIONAL ETHICS TO BUSINESS SATISFACTION (STUDY OF SME IN SOUTH SULAWESI) - Idrus Taba; Muhammad Ismail; Muhammad Sobarsyah; Tasrim Tasrim (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2019)
Organizational ethics plays an important role in shaping a good climate for all members of the organization. The ethical issues concerning to social problem, protection of the rights of employees, public society (social responsibility) and also consumers. The application of ethics in organization raises the employee job satisfaction (seeorganizational justice theory and cognitive dissonance theory). This study was analyzed using multiple regression method by taking the object of research on 350 SME businesses in three regencies, East Luwu, Bone and Tana Toraja in South Sulawesi. This study was focused in three forms, namely egoistic ethical climate, benevolent, and principled ethical climate. The results of the study show that organizational climate is like egoistic ethics climate and benevolence ethical climate the organization does not show positive results on employee job satisfaction. However, the coefficient of egoistic climate has negative influence to job satisfaction. Whereas principled ethical climate shows a positive and significant influence on employee job satisfaction.